Effects of boron omission and foliar fertilization on nutrition efficiency and production of Cowpea - Silva, Sylvia Letícia Oliveira [UNESP]; Prado, Renato de Mello [UNESP]; da Silva, Gilmara Pereira [UNESP]; da Silva Jéunior, Gabriel Barbosa [UNESP]; Rossi, Monica Lanzoni; Gonzéalez, Leéonides Castellanos [UNESP] (American Society for Horticultural Science, 2018)
This study aimed to evaluate the effects of boron (B) omission on cowpea nutrition and to compare the impact of foliar B fertilization with and without sorbitol on cowpea growth, nutritional status, and B uptake. Two trials using a completely randomized experimental design were conducted. During the first experiment, nutrient solution was provided without B (LB) and with B (+B) in 10 replicates. During the second experiment, a 5 x 2 factorial treatment scheme was used. Five B concentrations (0, 1.25, 2.5, 3.75, and 5.0 g·LL1) were administered foliarly in the form of boric acid with or without sorbitol (500 mmol·LL1) in four replicates. B omission symptoms, root growth, plant organ dry mass and B content, and grain yield were evaluated. B omission induced greater losses in reproductive organ and root growth than in leaf and stem production. It also caused deformation of the middle lamella and accumulation of starch in the chloroplasts. Foliar applications of 2.6 to 2.9 g·LL1 B improved cowpea production. The addition of sorbitol did not enhance plant growth. However, it increased B absorption in the vegetative parts of the plant but did not enhance seed production.
Keywords: Crop quality; Nutrient management; Plant nutrition; Sorbitol; Vigna unguiculata